Genetic Testing and Clinical Management Practices for Variants in Non-BRCA1/2 Breast (and Breast/Ovarian) Cancer Susceptibility Genes: An International Survey by the Evidence-Based Network for the Interpretation of Germline Mutant Alleles (ENIGMA) Clinical Working Group - Nielsen, Sarah M; Eccles, Diana M; Romero, Iris L; Al-Mulla, Fahd; Balmaña, Judith; Biancolella, Michela; Bslok, Rien; Caligo, Maria Adelaide; Calvello, Mariarosaria; Capone, Gabriele Lorenzo; Cavalli, Pietro; Chan, T L Chris; et al. (JCO precision oncology, 2018)
PURPOSE: To describe a snapshot of international genetic testing practices, specifically regarding the use of multigene panels, for hereditary breast/ovarian cancers. We conducted a survey through the Evidence-Based Network for the Interpretation of Germline Mutant Alleles (ENIGMA) consortium, covering questions about 16 non-BRCA1/2 genes. METHODS: Data were collected via in-person and paper/electronic surveys. ENIGMA members from around the world were invited to participate. Additional information was collected via country networks in the United Kingdom and in Italy. RESULTS: Responses from 61 cancer genetics practices across 20 countries showed that 16 genes were tested by > 50% of the centers, but only six (PALB2, TP53, PTEN, CHEK2, ATM, and BRIP1) were tested regularly. US centers tested the genes most often, whereas United Kingdom and Italian centers with no direct ENIGMA affiliation at the time of the survey were the least likely to regularly test them. Most centers tested the 16 genes through multigene panels; some centers tested TP53, PTEN, and other cancer syndrome-associated genes individually. Most centers reported (likely) pathogenic variants to patients and would test family members for such variants. Gene-specific guidelines for breast and ovarian cancer risk management were limited and differed among countries, especially with regard to starting age and type of imaging and risk-reducing surgery recommendations. CONCLUSION: Currently, a small number of genes beyond BRCA1/2 are routinely analyzed worldwide, and management guidelines are limited and largely based on expert opinion. To attain clinical implementation of multigene panel testing through evidence-based management practices, it is paramount that clinicians (and patients) participate in international initiatives that share panel testing data, interpret sequence variants, and collect prospective data to underpin risk estimates and evaluate the outcome of risk intervention strategies.